On-site inspection as a tool for developing auditing skills in engineering: integrating continuous education contents into higher education programs - García-García, Rebeca María; García-Caballero, Cristal Alejandra; Villarreal-Lara, Raúl; Mirón-Mérida, Vicente Antonio (Frontiers in Education, 2024)
Employability has been a priority for higher education institutions, and some skills, such as auditing skills, are necessary for students to enter into work life. In this regard, auditing skills can be applied in the food industry in different areas such as production, food safety, quality assurance, and environmental responsibility. Developing these skills could take years of practice and the completion of several courses, certifications, and diplomas, increasing the existing gap regarding auditing skills. In this work, 25 students from a Design of Process and Food Safety Management Systems class implemented a Food Safety and Food Quality checklist based on the Mexican regulation NOM-251-SSA1-2009 Hygiene Practices for Food, Beverage, and Supplement Processing, to analyze a real-life challenge in a beverage company that participated as a Training Partner. Two soft skills were evaluated: decision-making and problem-solving. The problemsolving effectiveness of these instruments was assessed by collecting the feedback of an experienced auditor and a representative from the audited company. The average result obtained for students after auditing the beverage company was 67.04, which was close to the assigned grade from the senior auditor (72.94), which indicates a good estimation from the instruments generated by the students. This exercise demonstrated the effectiveness of the students in performing accordingly and delivering the expected outcomes in front of a real industrial challenge. The combination of continuous education with a work-based challenge functioned as a laboratory for the students, where they can obtain technical skills in combination with fundamental, personal, and cooperative skills, which are necessary for facing industry challenges in an environment of globalization.